AB1395 Switching from adalimumab to other disease-modifying antirheumatic drugs without apparent medical reasons in rheumatoid arthritis: Impact on health care service use. (23rd January 2014) - Signorovitch, J.; Bao, Y.; Samuelson, T.; Mulani, P.M.
Abstract : Background: Patients with rheumatoid arthritis (RA) stabilized on adalimumab (ADA) might be incentivized to switch from ADA to a different therapy with a lesser copayment even without apparent intolerance or lack of efficacy with ADA treatment. Objectives: To assess the impact of switching for no apparent medical reasons on health care service use in patients with RA stabilized on ADA therapy in a real-world setting. Methods: Adults with ≥2 RA diagnoses and ≥90 days of continuous ADA use were identified from the Thomson Reuters MarketScan® database (2003–2010). Patients who subsequently switched from ADA to a different disease-modifying antirheumatic drug (DMARD) with a ≥5% copayment decrease were defined as nonmedical switchers, with the fill date for the switched-to DMARD as the index date. The index fill date was required to be within 90 days after the last ADA prescription, and there had to be no other fills in the prior 6 months. Patients who subsequently refilled a prescription for ADA within 90 days were defined as maintainers, with the refill date as the index date. No direct measure of disease activity or ADA intolerance is available in the claims data. Therefore, in order to identify patients who apparently tolerated ADA therapy and had disease control, both cohorts were required to have no hospitalizations, emergency department visits, or use of oral/injectable corticosteroids in the 6 months before the index date. Data analyses were performed for the 6-month period after the index date. Use of health care services and rates of treatment discontinuation (ie, ≥90-day gap in prescription fills) were compared between nonmedical switchers and maintainers using multivariate Poisson and Cox proportional-hazards multivariate regression models, respectively, adjusting for demographics, health care resource use and costs, and comorbidities identified in the 6-month period before the index date. Results: A total of 6270 patients were identified as maintainers and 342 as nonmedical switchers. Of the 342 nonmedical switchers, 176 (51%) switched to another TNF antagonist and 166 (49%) switched to nonbiologic DMARDs. On average, nonmedical switchers decreased their monthly copayments by 36.2 or 43.9 if they switched to a nonbiologic DMARD or another TNF antagonist, respectively. Compared with maintainers, nonmedical switchers incurred 42% more emergency department visits (incidence rate ratio [IRR]=1.42, 95% confidence interval [CI]=1.07–1.88; P =.015) and 12% more outpatient visits (IRR=1.12, 95% CI=1.09–1.16; P <.001) for any conditions. For RA-related health care services, nonmedical switchers had 14% more outpatient visits (IRR=1.14, 95% CI=1.07–1.22) and 29% more rheumatologist visits (IRR=1.29, 95% CI=1.18–1.42) than did maintainers (both P <.001). Nonmedical switchers were more likely to discontinue the new DMARD compared with the ADA discontinuation rate among maintainers (hazard ratio=1.34, 95% CI=1.15–1.57; P <.001) in the 6-month period after index. Conclusions: Among patients with RA stabilized on ADA, those who switched to another DMARD therapy for no apparent medical reason other than lower out-of-pocket costs used significantly more health care services compared with those who maintained ADA therapy. Disclosure of Interest: J. Signorovitch Consultant for: Abbott (contract with Analysis Group), Employee of: Analysis Group, Y. Bao Shareholder of: Abbott, Employee of: Abbott, T. Samuelson Consultant for: Abbott (contract with Analysis Group), Employee of: Analysis Group, P. Mulani Shareholder of: Abbott, Employee of: Abbott